Exploration of benign deep eutectic solvent–water systems for the highly efficient production of furfurylamine from sugarcane bagasse via chemoenzymatic cascade catalysis. Issue 20 (29th September 2021) - Li, Qing; Di, Junhua; Liao, Xiaolong; Ni, Jiacheng; Li, Qi; He, Yu-Cai; Ma, Cuiluan
Abstract : A benign deep eutectic solvent–water system for the highly efficient production of furfurylamine from sugarcane bagasse via chemoenzymatic cascade catalysis. Abstract : Recently, cost-effective production of high value-added furan chemicals from abundant and renewable bioresources has attracted much attention via a chemoenzymatic approach in an environmentally friendly reaction system. In this work, a chemoenzymatic cascade reaction for bridging tandem chemocatalysis and biocatalysis was constructed to valorize biomass into furfurylamine in a deep eutectic solvent (DES)–water system. Waste shrimp shell (SS) was used as a biobased carrier to prepare sulfonated tin-based solid acid (Sn-SS) for catalyzing sugarcane bagasse (SB) into furfural in DES–water. The prepared Sn-SS was characterized by XRD, SEM, FTIR spectroscopy and BET. Furfural (113.2 mM) was obtained in 62.3% yield from xylan in SB by Sn-SS (0.6 wt% dose) within 20 min at 170 °C in [ChCl][EG]–water (20 : 80, v : v). A potential catalytic mechanism was proposed for catalyzing SB into FAL and derivatives in [ChCl][EG]–water. Sequentially, one newly constructed recombinant Escherichia coli PRSFDuet-CV-AlaDH cells containing ω-transaminase and l -alanine dehydrogenase were used for the biological transamination of SB-derived furfural to furfurylamine in the presence of amine donor NH4 Cl (2.0 mol NH4 Cl/mol furfural) and cosubstrate glucose (1.0 mol glucose/mol furfural) at 35 °C and pH 8.0 without the removal of Sn-SS and residual SB. Within 1 h, SB-derived furfural was wholly aminated to furfurylamine with a productivity of 0.458 g furfurylamine per g xylan in SB by whole cells using NH4 Cl as an amine donor in [ChCl][EG]–water (20 : 80, v : v). It was found that [ChCl][EG]–water enhanced furfural and furfurylamine yields. Compared to the aqueous system, this green [ChCl][EG]–water (20 : 80, v : v) system enabled the highly efficient production of furfurylamine from SB via chemoenzymatic cascade catalysis with a sulfonated Sn-SS catalyst and ω-transaminase biocatalyst by enhancing the catalytic activity and thermostability of chemocatalysts and biocatalysts. This chemoenzymatic cascade reaction strategy had potential application for utilizing renewable biomass into furan-based chemicals in the benign DES–water system.